Tempeh spice juice on the increasing haemoglobin levels toward adolescents girl: - Endah Yulianingsih; Febri Dwi Yanti (Jurnal Kesehatan Ibu dan Anak, 2021)
The incidence of anemia toward adolescent girls has reached 26.4% caused by adolescent girls who have irregular eating habits, consume risky foods such as fast food, snacks and soft drinks and their high desire to diet to look slim which affects their intake of nutrients including sources of Fe. The purpose of this study is to determine the effect of tempeh spice juice on increasing hemoglobin levels toward adolescent girls. The study design was pre-experimental quantitative by using the one group pretest test-posttest design. The study subjects were 30 adolescent girls who were included in the inclusion criteria. There was a difference in hemoglobin level of adolescents before (mean= 13.123; SD=2.2624) and after (mean=13.910; SD=1.5372) consuming tempeh spice juice(p-value=0.002). Tempeh spice juice can increase the hemoglobin level of adolescent girls.